The Implementation of Peer Feedback Strategy in Teaching Recount Text - Mualifah, Siti (RETAIN, 2021)
Peer feedback could be a strategy that can be implemented by the teachers, especially in teaching writing. The steps of peer feedback strategy enable students to finish their assignments with their peers. They can contribute to their peers’ drafts for a better final draft. However, some problems were faced by students in giving feedback such as lack of grammatical knowledge, have limited English vocabularies to give feedback and difficult to understand the instruction. This study is conducted through qualitative design to describe the implementation of peer feedback strategy in teaching Recount text. The subject of this study is a teacher of tenth graders of Vocational High School 1 Driyorejo, Gresik. The research instruments are field notes and interviews. Moreover, the result appears that the steps in actualizing peer feedback strategy in teaching writing Recount text are (1) Pre-peer feedback included brainstorming, introducing peer feedback in writing, writing a draft, and training the peer feedback process (2) While-peer feedback where students begin their peer feedback while the teacher monitors and helps students while doing peer feedback process (3) Post-peer feedback where students get their draft and proceed to reexamine their draft based on their peer criticism. Furthermore, the problems in executing peer feedback strategy in educating writing Recount text are students’ characteristics, creating active peer feedback groups, and setting up the training section as the guidance of peer feedback strategy.Keywords: peer feedback, teaching writing, recount text.